Diseño de una herramienta digital para la detección de los cambios en los costos de eventos con NPT (tiempos no productivos) en la perforación de pozos de hidrocarburos usando Data Analyzer: caso de estudio Cuenca de Santos, Brasil (2022)
This document aims to present the design and development of a digital tool that allows the detection of changes in the costs of events with non-productive times (NPT) during the drilling of hydrocarbon wells, making a report in which the information obtained is presented in a friendly manner, facilitating the understanding.